2007
DOI: 10.1007/s00122-007-0546-9
|View full text |Cite
|
Sign up to set email alerts
|

Tagging QTLs for late blight resistance and plant maturity from diploid wild relatives in a cultivated potato (Solanum tuberosum) background

Abstract: Phytophthora infestans causes an economically important disease of potato called late blight. The epidemic is controlled chemically but resistant potatoes can become an environment-friendly and Wnancially justiWed alternative solution. The use of diploid Solanum tuberosum derived from European tetraploid cultivars enabled the introgression of novel genes encoding foliage resistance and tuber resistance from other species into the modern cultivated potato gene pool. This study evaluated the resistance of the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Few studies have analyzed quantitative trait loci (QTL) for resistance and plant maturity in the same mapping population (Collins et al 1999;Oberhagemann et al 1999;Visker et al 2003;Bormann et al 2004;Bradshaw et al 2004;Sliwka et al 2007). These experiments showed that many QTL for resistance to late blight colocalize with QTL for plant maturity, which explains the phenotypic correlation observed between these traits.…”
mentioning
confidence: 99%
“…Few studies have analyzed quantitative trait loci (QTL) for resistance and plant maturity in the same mapping population (Collins et al 1999;Oberhagemann et al 1999;Visker et al 2003;Bormann et al 2004;Bradshaw et al 2004;Sliwka et al 2007). These experiments showed that many QTL for resistance to late blight colocalize with QTL for plant maturity, which explains the phenotypic correlation observed between these traits.…”
mentioning
confidence: 99%
“…Although high levels of misclassification were observed for all three measures, some were more accurate than others. We found measures of flowering development to be highly inaccurate, even though they are a common component of various maturity screening protocols [2,[4][5][6]. Peroxidase measures were slightly better, but the optimal period of time to assess this trait was variable across locations.…”
Section: Discussionmentioning
confidence: 98%
“…Flowering is a physiological attribute commonly utilized by potato breeders for evaluating maturity [2,[4][5][6]. Abundant flowering has been correlated with delayed tuber bulking [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the TPT marker is being studied in ber-progenies. This marker is located on Chromosome 10 linked to a QTL for resistance in leaflets which accounted for 15.6% of the variance in resistance (Sliwka et al 2007). Based on the results obtained from a t-test, the difference of the means is considered to be statistically significant.…”
Section: Developing Populations and Marker-assisted Breeding For Disementioning
confidence: 98%